Retrospective analyses of stability and variability in relative age effects of handball talents over seventeen years - Schorer, J.; Büsch, D.; Faber, I.; Wattie, N. (Sports Medicine - Open, 2025)
In the last thirty years research on relative age effects (RAEs) has exploded in numbers. However, the stability and variability of these effects have hardly been investigated. The three aims of this retrospective study were first to investigate the stability and variability of RAEs over 17 years, second to compare these effects for young female and male athletes, and third to compare these effects between selected and non-selected athletes relative to variability estimates from 17 years prior to assess possible changes in athlete development trends. For this study, birth dates were provided for all participants of the talent selection camps by the German Handball Federation from 2008 to 2024. Results show that first while some variability was observed, the effects remained stable. Second, there are only small differences between sexes in general, although these increased with selection. And thirdly, that selections create stronger effects for male athletes, but not for female ones. Taken together, this study provides an interesting picture of the variability and stability of relative age effects over 17 years.